Rheological Behavior of Polymer-Clay Nanocomposite Hydrogels: Effect of Nanoscale Interactions - ABDURRAHMANOĞLU, SUZAN (WILEY, 2010)
This research highlights different viscoelastic responses of polymer-clay nanocomposite hydrogels depending on the type of the monomer used in their preparation. Polymerization reactions of N,N-dimethylacrylamide (DMA), N-isopropylacrylamide (NIPA), and acrylamide (AAm) in aqueous clay (Laponite) dispersions have been investigated by rheometry using oscillatory deformation tests. The gelation profile of AAm polymerization obeys typical gelation kinetics, while a reverse behavior was observed during the DMA or NIPA polymerizations. In the latter cases, after an abrupt increase in elastic and viscous moduli at the start of the reaction, they both decrease continuously during the Whole Worse of the gelation process. Creep-recovery tests performed on the final hydrogels indicate that the time-dependent viscoelastic response of the gels derived from AAm is distinctly different from the other gels. The retardation time of AAm gel is about twice that of DMA or NIPA gels indicating higher mobility of the crosslink zones in the former gel. As a consequence, a larger amount of energy is dissipated during the deformation of nanocomposite hydrogels based on AAm. Different extent of interactions between the clay particles and the monomers explains the results of observations. (C) 2010 Wiley Periodicals, Inc. J Appl Polym Sci 116: 2328-2335, 2010
Keywords: nanocomposite hydrogels; clay; rheology; LAPONITE DISPERSIONS; SWELLING BEHAVIOR; ELASTICITY; COPOLYMERS; SCATTERING